2023
DOI: 10.1007/s00109-023-02289-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of aryl hydrocarbon receptor (AhR) in Alzheimer’s disease: role of tryptophan metabolites generated by gut host-microbiota

Abstract: Gut microbiota in interaction with intestinal host tissues influences many brain functions and microbial dysbiosis has been linked with brain disorders, such as neuropsychiatric conditions and Alzheimer’s disease (AD). l-tryptophan metabolites and short-chained fatty acids (SCFA) are major messengers in the microbiota-brain axis. Aryl hydrocarbon receptors (AhR) are main targets of tryptophan metabolites in brain microvessels which possess an enriched expression of AhR protein. The Ah receptor is an evolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 231 publications
1
31
0
Order By: Relevance
“…In Alzheimer's disease (AD), the dysregulated gut microbes produced large amounts of tryptophan metabolites that activate AhR signalling in the brain, disrupting the blood-brain barrier and promoting inflammation and AD pathology. 57 Human umbilical mesenchymal stem cells (HUMSCs) cured collagen-induced arthritis (CIA) in mice by modulating the interplay between host immunity and gut microbiota via the AhR. 58 It suggested that AhR is essential for the control of immune responses and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease (AD), the dysregulated gut microbes produced large amounts of tryptophan metabolites that activate AhR signalling in the brain, disrupting the blood-brain barrier and promoting inflammation and AD pathology. 57 Human umbilical mesenchymal stem cells (HUMSCs) cured collagen-induced arthritis (CIA) in mice by modulating the interplay between host immunity and gut microbiota via the AhR. 58 It suggested that AhR is essential for the control of immune responses and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The aryl hydrocarbon receptor (AhR) is an evolutionarily conserved, ligand-regulated transcription factor which is not only a major sensor of environmental toxins but it is also activated by a number of metabolites ranging from heme, arachidonic acid, and kynurenine pathways as well as indoles from microbiota [ 155 , 156 ]. AhR signaling cooperates closely with indoleamine 2,3-dioxygenase 1 (IDO1), a common immune checkpoint, in the regulation of the aging process [ 157 , 158 ].…”
Section: The Aging-associated Signaling Stimulates the Expression Of ...mentioning
confidence: 99%
“…Moreover, Wang et al [ 161 ] reported that the inhibition of AhR signaling potentiated the therapeutic response induced with anti-PD-L1 antibody treatment in mouse lung cancer model. Tryptophan metabolites, e.g., compounds produced via the kynurenine, indole, serotoinin, or tryptamine pathways, are activators of AhR signaling as well as immune modulators [ 156 , 164 ]. Currently, there is clear evidence that the gut microbiota can modulate the efficacy of anti-PD-1/PD-L1 therapy both in humans and mice [ 165 ].…”
Section: The Aging-associated Signaling Stimulates the Expression Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptophan is an essential amino acid for humans commonly found in everyday diets. Recently the roles of tryptophan metabolites in disease development have been reported in various diseases, including MAFLD [ 71 ], dermatological diseases [ 72 ], neurodegenerative diseases [ 73 ] and kidney diseases [ 74 ]. Tryptophan can be metabolized through the following pathways in the human gut: the kynurenine pathway (90%–95% of tryptophan metabolism), the serotonin/melatonin pathway (1%–2%), and indole pathway (5%) [ 71 ].…”
Section: Icrobial Metabolites On Metabolic-associated Fatty Liver Dis...mentioning
confidence: 99%